Spiritual Guidance and Mindful Worship: An Intervention Study within School Counseling Services - Fika Amalia; Akhmad Rudi Masrukhin (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2026)
his study examines the role of spiritual guidance within school counseling services in strengthening students’ mindful worship. The school has implemented systematic religious habituation programs; however, variations in students’ inner awareness remain evident. Using a one-group pretest–posttest design, the study employed an empirical needs assessment as the pretest and a posttest administered after the implementation of structured spiritual guidance sessions. Participants were 31 eleventh-grade students. Data were collected using a 48-item mindful worship scale covering cognitive awareness, attentional presence, emotional–spiritual engagement, and behavioral integration. Data analysis included descriptive statistics, Shapiro–Wilk normality testing, reliability analysis, and paired-sample t-testing. The findings indicate a statistically significant increase in mindful worship scores after the intervention sessions, with data meeting assumptions of normality and demonstrating high internal consistency. The results suggest that spiritual guidance in school counseling can meaningfully complement institutional habituation by deepening students’ inner awareness of worship. This study contributes preliminary empirical support here.